ЗВІДКИ ПРИХОДИТЬ ПРОБЛЕМА ЗДОРОВ'Я (Педагогіка вищої та середньої школи, 2004)
Consciousness forms the certain emotional a fettle conditions, which through biochemical mechanisms influence on physical fettle of the person. Public thought is not directed toward shaping the image of a cheerful personality, as an ideal one. Every day, official and business relations exclude smile, as attribute of the communication contact. Education does not teach self-upbringing constant and firm positive emotional condition, the personal responsibility for its "emotional wellbeing wellness".